THE RELATIONSHIP BETWEEN RISK AND COST OF QUALITY: THE CASE OF JESSE LANGFORD - Süleyman YÜKÇÜ; Selda KORGA (Prizren Social Science Journal, 2023)
Risk permeates every moment of life, impacting both individuals and businesses through their activities. While certain risks encountered have a minimal likelihood of materializing, others possess a considerable probability. Preventing risks in life entails averting failures. The most effective approach to preventing failures, both in business and all aspects of life, is through proactive measures that eliminate the underlying causes of failure before they occur. Engaging in prevention activities is invariably more cost-effective than dealing with the potential consequences and expenses associated with failures. In situations where the risk's realization probability is high, preventive measures can be implemented to mitigate or prevent it altogether. Consequently, by actively addressing risks, failures can be averted through risk prevention.